BUILDING TECHNICAL SERVICE ONTOLOGY IN AGROINDUSTRIAL COMPLEX - Valery P. Dimitrov; Lyudmila V. Borisova; Boris B. Zhmaylov (Advanced Engineering Research)
Knowledge space and basic concepts of the technical service in the agroindustrial complex are determined on the basis of the process-system approach. The taxonomic class hierarchy ontological model using OWL-diagram and the approach to the metadata content generation for its representation are offered. Protege platform has been used as an instrument.